Impact of dividend policy, capital structure, and profitability on consumer goods firm value: Role of firm size (2013-2022) - Samuel Dunant Siregar; Nagian Toni; Yeni Ariesa (Privietlab, 2023)
This study aims to analyze the effects of Dividend Policy, Capital Structure, and Profitability on the Firm value in the Consumer Goods sector on the Stock Exchange during the period 2013–2022. Firm size was utilized as a moderating variable. The dependent variable in this research is Firm value (Tobin's Q), whereas the moderating variable is Firm size. The population for this study was drawn from the Consumer Goods sector on the Stock Exchange for the 2013–2022 period. Out of a total population of 51 companies, 31 met the sample criteria. Two research methods were employed: the panel data regression test and the Moderated Regression Analysis (MRA). The results from the panel data regression test, using the Fixed Effect Model (FEM) method, indicate that, collectively, dividend policy, capital structure, and profitability influence the firm’s value. Individually, both dividend policy and profitability positively influence the firm’s value, while the capital structure variable does not have a significant effect. Moreover, the Moderated Regression Analysis (MRA) demonstrates that the firm size variable acts as a moderator, influencing the relationships between dividend policy, capital structure, profitability, and firm value.